https://www.zhihu.com/question/454994240
方法一
方法二
上面的证明结论是
$x^m-x-1$不可约
$x^m-x+1$当$m=3k, 3k+1$时不可约
综合10#立刻得到
$f(x)=x^{6k+5} - x \pm 1, k \ge 0$不可约
$f(x)=x^{6k+2} \pm x - 1, k \ge 1$不可约
令$m=6k$
带入$-x$
$x^{6k}-x-1$不可约得到$x^{6k}+x-1$不可约
$x^{6k}-x+1$不可约得到$x^{6k}+x+1$不可约
令$m=6k+4$
带入$-x$
$x^{6k+4}-x-1$不可约得到$x^{6k+4}+x-1$不可约
$x^{6k+4}-x+1$不可约得到$x^{6k+4}+x+1$不可约
令$m=6k+1, 6k+3$
带入$-x$,易知
$x^m+x-1$当且仅当$x^m+x+1$不可约
由11#定理3.10.3
$f(x)=x^m+x+1$与$f^{\star}(x)=x^m+x^{m-1}+1$若有公共根,
则$x=x^{m-1}$,即$x^{m-2}=1$,易知$x=1$不是两个的公共根
带入$f^{\star}(x)$得到$x^2+x+1=0$,即$x^3=1$
简单检验得知当$m=6k+1, 6k+3$时,$x^3=1$均不满足$f(x)=0$与$f(x), f^{\star}(x)$有公共根矛盾
即$m=6k+1, 6k+3$时,$x^m+x\pm1$不可约
即$x^m \pm x \pm 1$当$m=3k, 3k+1$时不可约
扩展7#的结论
$f(x) = x^m \pm nx \pm 1 \in \ZZ, m, n \in \ZZ, m >= 2, n >= 1$仅有如下形式可约
$x^2+2x+1$
$x^2-2x+1$
$x^{6k+2} \pm x+1, k>=1$
$x^{6k+5}+x \pm 1, k>=0$
页:
1
[2]